Thriving or Surviving? Raising Our Ambition for Trans Children in Primary and Secondary Schools - Horton, Cal (Frontiers in Sociology, 2020)
As more trans children find the confidence to make themselves known in our primary and secondary schools, school teachers and administrators look for guidance on how to best support trans pupils. This article synthesises findings from global literature on trans children in primary and secondary education (K1-12 in the US), extracting key themes and conclusions. It then examines the most recent UK school guidance documents on trans inclusion, assessing which lessons and recommendations from global literature are represented. The article highlights existing good practices in visibility and representation and in protection from violence and harassment. Several areas where additional effort is needed are identified, including action on environmental stress and cisnormativity, addressing barriers to school trans-inclusivity and institutional accountability. A number of important shifts are called for: from adaptation on request to pre-emptive change; from accommodation to a rights-based approach; from pathologisation to trans-positivity. Finally, the article raises expectations on what it means to be an ally for trans children in education.